Synergy between infection control and antimicrobial stewardship programs to control carbapenem-resistant Enterobacterales - Wanda Cornistein; Daniela Santonato; Paula Andrea Novau; Leonardo Guillermo Fabbro; Melisa Fernanda Jorge; Maria Agustina Malvicini; Viviana Vilches; Fernando Martin Iudica (Cambridge University Press, 2023)
Abstract Objective: Argentina is the third country in the world with the higher levels of CRE. The primary objective is to achieve an optimal result in the CRE infection rate after the implementation of an IPC program and antimicrobial stewardship programs (ASP) in a large teaching hospital in Argentina. Methods: Retrospective, observational study from January 2018 to December 2021, in a 220-bed tertiary care teaching hospital in Buenos Aires province. Actions aimed at CRE control and prevention included CRE and healthcare-associated infection (HAI) surveillance; compliance with hand hygiene, hospital hygiene, contact isolation precautions, and care bundles for the prevention of device-associated infections; optimization of antimicrobial treatments, antimicrobial consumption, education, and feedback. Results: Synergy between an ICP and ASP achieved controlled rate of CRE infections reaching the lowest levels during 2020 (0.08 episodes/1000 patient days). Colonization rate remained stable throughout the study period. Ventilator-associated pneumonia (VAP) rate showed a trend toward lower rates. Compliance with care bundles showed rates >85%. Antimicrobial consumption increased slightly during the study period (15%). Among high-impact antimicrobials, only colistin consumption increased. Conclusion: Our study demonstrates the sustained and beneficial impact of an IPC Program and an ASP to control CRE infection.